Open source posturography. - Rey-Martinez, Jorge; Pérez-Fernández, Nicolás (Acta Oto-Laryngologica, 2016)
Conclusion: The proposed validation goal of 0.9 in intra-class correlation coefficient was reached with the results of this study. With the obtained results we consider that the developed software (RombergLab) is a validated balance assessment software. The reliability of this software is dependent of the used force platform technical specifications. Objective: Develop and validate a posturography software and share its source code in open source terms. Methods: Prospective non-randomized validation study: 20 consecutive adults underwent two balance assessment tests, six condition posturography was performed using a clinical approved software and force platform and the same conditions were measured using the new developed open source software using a low cost force platform. Intra-class correlation index of the sway area obtained from the center of pressure variations in both devices for the six conditions was the main variable used for validation. Results: Excellent concordance between RombergLab and clinical approved force platform was obtained (intra-class correlation coefficient =0.94). A Bland and Altman graphic concordance plot was also obtained. The source code used to develop RombergLab was published in open source terms.